Evaluation of the Cutaneous Lymphoma International Prognostic Index in patients with early stage mycosis fungoides - Gustavo Moreira Amorim; João Paulo Niemeyer Corbellini; Danielle Carvalho Quintella; Tullia Cuzzi; Márcia Ramos- (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Mycosis fungoides (MF) is the most common subtype of cutaneous T-cell lymphoma. TNMB system is the staging method used in MF, and it not only guides therapeutic management, but represents the main prognostic factor. In order to improve the prognostic evaluation, the Cutaneous Lymphoma International Prognostic Index (CLIPi) was proposed. Objective: To evaluate the performance of CLIPi score for prognostic analysis in patients with early stage MF. Methods: This is a retrospective cross-sectional observational study, with exploratory analysis. The outcome variables were disease progression and related death. Results: One hundred and two patients were stratified according to CLIPi score, being the majority classified as low risk. Patients with intermediate or high risk presented disease progression more frequently than those with low risk (PR: 1.2 / p = 0.004 / 95%CI: 1.0 - 1.6). The same did not occur with the variable related death. In addition, survival rates were not consistent with risk stratification. Study Limitations: Small sample and its retrospective analysis. Conclusions: Since CLIPi score was proposed, four other studies that we could consult showed conflicting results, similar to the present study. Further studies are necessary for a recommendation of its use.